دور الحوكمة في تعزيز الإدارة الخضراء والمسؤولية الاجتماعية لتحقيق التنمية المستدامة (Comprehensive Journal of Science, 2025)
This study highlights the role of good governance in promoting green management and corporate social responsibility (CSR) as key mechanisms for achieving sustainable development. Using a theoretical analytical approach based on relevant literature and previous studies, the research finds that governance provides a framework ensuring transparency and accountability while supporting environmentally and socially responsible practices.The study concludes that integrating governance with green management and CSR enhances institutional performance and contributes to achieving a balance among the economic, social, and environmental dimensions of sustainable development.
Keywords: Governance, Green Management, Corporate Social Responsibility, Sustainable Development